Antibacterial and Antibiofilm Activity of Pineapple Jelly Candy Sweetened with Stevia Against S. mutans - Tyas Hestiningsih; Martha Mozartha; Anisya Putri Cahyani; Nurul Uzma; Rosada Sintya Dwi; Ulfa Yasmin (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2026)
Introduction: Streptococcus mutans is the main cause of dental caries. Pineapple and stevia exhibit antibacterial activity against S. mutans. Their combination can be formulated into a non-cariogenic jelly candy. Purposes: To investigate the antibacterial and antibiofilm effects of jelly candy formulated with pineapple and stevia against S. mutans. Methods: This study used an in vitro experimental design with a post-test only control group design. The antibacterial activity was assessed using the agar well diffusion method, while the antibiofilm activity was evaluated using the microtiter plate method. The experimental groups consisted of pineapple and stevia jelly candy, stevia jelly candy without pineapple, and a negative control group (jelly candy without pineapple and stevia). Antibacterial activity was determined by measuring the diameter of the inhibition zone, whereas antibiofilm activity was assessed by measuring absorbance or optical density values. Data from each test were analysed using Welch’s ANOVA and One-Way ANOVA tests. Results: Welch’s ANOVA analysis of inhibition zone diameters among groups demonstrated a significant difference (p < 0.05). The largest inhibition zone was observed in the pineapple and stevia jelly candy group (10.72 mm). The One-Way ANOVA results also revealed significant differences in absorbance values among all groups (p < 0.05). Pineapple and stevia jelly candy group exhibited the lowest absorbance value compared with other groups. Conclusion: Pineapple and stevia jelly candy possessed antibacterial and antibiofilm activities against S. mutans.